Analysis of the National Formulary Drug Supply Chain with Its Availability in the Pharmacy Installation of the Government General Hospital (RSUP) Dr. Sitanala Tangerang City - Hercien Hercien; Mutia Mutia; Idrus Idrus (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
This study explores the pharmaceutical supply chain management of the National Formulary at RSUP Dr. Sitanala in Tangerang City, aiming to identify obstacles to drug availability and formulate effective and efficient solutions. Acknowledging quality healthcare as a fundamental human right and a critical investment for a nation's future, this research emphasizes the importance of high-quality healthcare services. These services encompass not only treatment but also health promotion and disease prevention through the adoption of clean and healthy living habits. Drug availability is a major pillar in the provision of quality healthcare services. Effective and efficient management of the pharmaceutical supply chain, particularly regarding National Formulary drugs, is crucial in ensuring the availability of medications at healthcare facilities. This research employs a comprehensive analysis of the supply chain processes at RSUP Dr. Sitanala, examining stages such as drug selection, demand planning, procurement, receipt, storage, distribution, drug control, therapy monitoring, prescription preparation, drug dispensation, and medication administration. The study's methodology involves a case study approach, integrating theoretical management principles and interdisciplinary pharmacy management with compliance to regulations, as outlined in Permenkes No. 76 of 2016. Findings from RSUP Dr. Sitanala indicate that the hospital's pharmaceutical management practices align with contemporary health and pharmacy management theories, emphasizing structured systems, stringent verification, and effective interprofessional communication to ensure medication safety and efficacy. The study identifies challenges in information technology and interdisciplinary coordination as areas needing improvement. Nonetheless, a commitment to continuous improvement and adherence to regulatory standards reflects RSUP Dr. Sitanala's dedication to enhancing the quality of pharmaceutical management and healthcare services. The implications of this research extend beyond RSUP Dr. Sitanala, offering valuable recommendations for improving drug supply chain management in other healthcare institutions in Indonesia. By enhancing access to and the quality of healthcare services, this study contributes to the broader goal of achieving the highest possible level of health for individuals, reflecting the perspective of human rights and investment in the nation's future health.